(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Illegal parking is a significant problem in urban areas, as it causes congestion, obstructs traffic flow, and poses safety hazards for pedestrians and motorists. In response, the local government of Novaliches Proper, Quezon City, implemented a prohibition of illegal parking in the area. This study aimed to evaluate the effectiveness of the prohibition as perceived by 30 respondents. The results showed that the majority of the respondents were aware of the prohibition of illegal parking in Novaliches Proper. Of these, they reported that they had observed a positive impact on traffic flow while noting improvements in pedestrian safety. However, some respondents still observed instances of illegal parking, reporting that it still occurred frequently. Moreover, some respondents suggested that stricter enforcement was needed to fully eliminate the problem of illegal parking. Specifically, the respondents suggested increasing fines and penalties for violators while recommending more frequent monitoring and enforcement by local authorities. The findings of this study indicate that the prohibition of illegal parking in Novaliches Proper has had a positive impact on traffic flow and pedestrian safety, as perceived by the majority of the respondents. This suggests that the local government’s policies and strategies related to illegal parking have been effective in achieving their intended goals. However, the fact that some respondents still observed instances of illegal parking suggests that further efforts are needed to ensure compliance and enforcement. Specifically, the suggestions made by the respondents for increasing fines and penalties, as well as more frequent monitoring and enforcement, could be useful in enhancing the local government’s efforts to address the problem of illegal parking.